2021
DOI: 10.3390/catal11121515
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Catalytic Hydrogen Peroxide Production from Hydroxylamine Oxidation on Modified Activated Carbon Fibers: The Role of Surface Chemistry

Abstract: Herein, direct production of hydrogen peroxide (H2O2) through hydroxylamine (NH2OH) oxidation by molecular oxygen was greatly enhanced over modified activated carbon fiber (ACF) catalysts. We revealed that the higher content of pyrrolic/pyridone nitrogen (N5) and carboxyl-anhydride oxygen could effectively promote the higher selectivity and yield of H2O2. By changing the volume ratio of the concentrated H2SO4 and HNO3, the content of N5 and surface oxygen containing groups on ACF were selectively tuned. The AC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…Their research revealed that the high SO 2 and H 2 O resistance of Pt/Keg-CeTi in CO oxidation was related to its stronger surface acidity, surface cerium and molybdenum species reduction, and lower SO 2 adsorption and transformation compared to Pt/CeTi and Pt/MoP-CeTi. In reference [11], an easy synthetic process for H 2 O 2 generation was described, and a new comprehension of the conception and mechanistic examination of metal-free N-and O-doped carbon materials were also provided. The content and type of surface functional groups were improved by treating the PAN-based ACF with concentrated mixed acid in different volume ratios.…”
Section: This Special Issuementioning
confidence: 99%
“…Their research revealed that the high SO 2 and H 2 O resistance of Pt/Keg-CeTi in CO oxidation was related to its stronger surface acidity, surface cerium and molybdenum species reduction, and lower SO 2 adsorption and transformation compared to Pt/CeTi and Pt/MoP-CeTi. In reference [11], an easy synthetic process for H 2 O 2 generation was described, and a new comprehension of the conception and mechanistic examination of metal-free N-and O-doped carbon materials were also provided. The content and type of surface functional groups were improved by treating the PAN-based ACF with concentrated mixed acid in different volume ratios.…”
Section: This Special Issuementioning
confidence: 99%